Artifical Intelligence in Cyber Security in Morocco - Zahra, Ayach Fatima; Supandi, Supandi; Wijayanto, Wijayanto (Sentra Cendekia, 2024)
: Morocco had more than 56,000 cyberattacks directed towards mobile devices, as to a recent report by Russian cybersecurity company Kaspersky. Attacks against mobile devices increased significantly worldwide in 2023, amounting to 33.7 million and rising at a sweeping yearly average of 52%. Documentation research is the methodology employed in this study. It is a method of qualitative research. This means that rather than quantifying data, it focuses on comprehending and interpreting human experiences, behaviors, and views. The researcher investigates text-based materials (such as journal articles and internet media) to gain a better understanding of artificial intelligence in cybersecurity. Morocco has made significant advances in cybersecurity thanks to the combined efforts of different stakeholders, including the government, law enforcement, regulatory authorities, cybersecurity groups, the commercial sector, academia, international partners, and civil society. These efforts began with the development of the first "National Strategy for Information Security and Digital Trust" in 2007. AI-powered solution that was introduced in 2023 in Morocco and uses machine learning to detect phishing attacks, asset vulnerabilities, compromised credentials and credit cards, fraudulent domains, and attempts at online brand impersonation. Morocco strengthens its R&D center in AI and cybersecurity in 2024 by cooperating with Oracle, the American technology powerhouse, to expand its research and development (R&D) capabilities in Morocco.This strategic undertaking seeks to amplify its workforce by recruiting 1,000 IT specialists. In conclusion, Morocco is making substantial progress in this field, merging technological breakthroughs with ethical standards and global collaboration. As the nation persists in innovating, its dedication to data security will be instrumental in shielding its digital future